Analysis of the Success of Revegetation in Reclamation Plant Growth Percentage Aspect in Tanah Bumbu Regency, South Kalimantan - Khanifa, Arrina (BUMI: International Journal of Environmental Reviews, 2024)
Mining is a vital activity for the management and utilization of natural resources, serving as a source of foreign exchange for national development. However, mining often causes environmental damage, necessitating reclamation and revegetation efforts. Revegetation can be considered a vegetative technique applied in rehabilitating lands damaged during mining. This study involved primary data collection, specifically measuring plant growth and calculating growth rates. The research results from 2021, 2022, and 2023 indicate a continuous increase in growth percentages, suggesting successful reclamation in the study area.